Efektifitas Model Pembelajaran Quantum Learning di Tinjau dari Metakognitif Fisika Siswa Di SMAN 48 Jakarta - Imas Ratna Emawati; Feli Cianda Adrin Burhendi; Nurhabibi Harahap; Sugianta Sugianta (Jurnal Pendidikan Fisika, 2020)
The focus of this research is on how effectively the quantum learning model affects the physics meta-cognitive skills of students at SMAN 48 Jakarta. The research population consisted of 30 students in the experimental class. This type of research is a type of experimental research that uses a quasi-experimental research design in the form of one-group pretest-posttest design. After being treated with a quantum learning model, it can be seen that there is a shift in students’ meta-cognitive abilities from skilled enough to skilled. This shows that there is a significant influence of the quantum learning model of learning on students’ meta-cognitive abilities which in turn makes students have excellent learning outcomes. This is also in accordance with statistical calculations where tcount = 2.98 and ttable = 1.69, it is known that if tcount> ttable, the hypothesis is accepted and the known quantum learning model influences students’ meta-cognitive abilities.